Encapsulated Organohydrogel Couplants for Wearable Ultrasounds - Xiaoru Dong; Zhi Yang; Chaoran Xu; Jun Zhao; Juntong Zhu; Haokun Yi; Hui Xu; Zhuo Li (Advanced Electronic Materials, 2025)
Abstract The couplant layer that transmits sound waves to the skin is essential for ultrasound imaging. Conventional liquid‐based couplants are unsuitable for wearable detectors, while polymer‐based dry couplants often suffer from high acoustic attenuation. Hydrogel‐based couplants possess ideal acoustic and mechanical properties; however, water evaporation restricts their application in long‐term monitoring. Current strategies to improve water retention, such as encapsulating hydrogels with elastomers, typically overlook the issue of curing shrinkage. This shrinkage induces a wrinkled interface between the elastomer and hydrogel, which can cause scattering and reflection of acoustic waves, thereby compromising ultrasound quality. To address this problem, a prefabricated hydrogel is employed as a template to mitigate the curing shrinkage at the interface. In the meantime, a large amount of glycerol is added to the template to form the organohydrogel, which reduces interactions between polymer chains, further minimizing curing shrinkage and resulting in a smooth interface. Additionally, the glycerol within the organohydrogel, combined with the external encapsulation layer, enhances long‐term water retention. The results demonstrate that the prepared couplants maintain stable attenuation coefficients and produce clear imaging over 8 days.